Studi Perencanaan Power Sequencer Berbasis Mikrokontroler Atmega 328p - Abidin, Zainal; Setiawan, Achmad Budi (UNIVERSITAS PGRI MADIUN, 2023)
Power sequencers are used in audio sound system accessories or PLC in factories or industries so that audio sound system accessories and production equipment in factories or industries can run sequentially according to the order of their functions. So that later there will be no malfunctions or errors in audio sound system accessories or production equipment in factories or industries that can result in losses and cause damage to audio sound system accessories and production equipment in the industry. However, the power sequencer that is used for audio sound system accessories at this time cannot be changed - change the delay value and cannot only turn on or turn off one channel. Â In this study, the researcher designed a power sequencer that can be changed the delay value and can be turned on off on one of the channels through the control of the android application so that later it is easy to operate when used